2020
DOI: 10.1186/s13075-019-2086-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating microRNAs with prevalent and incident knee osteoarthritis in women: the OFELY study

Abstract: ObjectivesIn the context of the scarcity of biomarkers for knee osteoarthritis (OA), we examined the associations of prevalent and incident OA with the expression levels of serum miRNAs in subjects with and without OA.MethodsWith a next-generation sequencing approach, we compared the miRome expression of 10 women with knee OA and 10 age-matched healthy subjects. By real-time qPCR, we analyzed the expression levels of 19 miRNAs at baseline selecting 43 women with prevalent knee OA (Kellgren Lawrence score of 2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
(59 reference statements)
2
49
0
Order By: Relevance
“…Therefore, we believe that miR-29c-3p is not a relevant serum biomarker after HTO, although it may be related to OA progression. Rousseau et al evaluated the association between circulating miRNAs and knee OA in women and reported no significant changes in miR-29c-3p levels, consistent with our results [31]. Many studies have revealed the role of miR-424-5p in cell-or tissue-based OA [32].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we believe that miR-29c-3p is not a relevant serum biomarker after HTO, although it may be related to OA progression. Rousseau et al evaluated the association between circulating miRNAs and knee OA in women and reported no significant changes in miR-29c-3p levels, consistent with our results [31]. Many studies have revealed the role of miR-424-5p in cell-or tissue-based OA [32].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, plasma levels of miR-126 have been found to be increased in OA vs. controls [112] and, after celecoxib treatment, decreased in non-clinical responders and increased in clinical responders [118]. Finally, higher plasma miR-186 levels have been detected both in OA vs. controls [112] and in incident OA over the next 4 years [117].…”
Section: Circulating Mirnas and Osteoarthritismentioning
confidence: 87%
“…In conclusion, circulating miR-136 and the combination of miR-486-5p, miR-122-5p, and miR-19b-3 have the highest diagnostic potential in distinguishing OA patients from healthy controls [113,115]. Among the above-described validate miRNAs, levels of miR-146a have been found to be increased both in plasma of OA vs. controls [112] and in serum of prevalent knee OA vs. controls [117]; while considering OA who received celecoxib treatment, plasma levels of miR-146a have been found to be increased in non-clinical responders and decreased in clinical responders [118]. Similarly, plasma levels of miR-126 have been found to be increased in OA vs. controls [112] and, after celecoxib treatment, decreased in non-clinical responders and increased in clinical responders [118].…”
Section: Circulating Mirnas and Osteoarthritismentioning
confidence: 95%
See 1 more Smart Citation
“…Given that OA is polygenic in nature, miRNA are seen as attractive therapeutic entities as they In women from the Os des Femmes de Lyon (OFELY) cohort, circulating miR-146a-5p and 186-5p were elevated in those with prevalent knee OA compared to healthy controls. In fact, the likelihood of prevalent knee OA increased with each quartile increase in serum miR-146a-5p [39]. Local levels of isoform miR-146a along with miR-140-5p were downregulated in human OA chondrocytes and associated with hypermethylation of the regulatory regions in these miRNAs [40].…”
Section: Oa Transcriptomics: Examining Phenotypesmentioning
confidence: 97%